1998
DOI: 10.1097/00004703-199802000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Adolescentsʼ Health Attitudes and Adherence to Treatment for Insulin-Dependent Diabetes Mellitus

Abstract: Adolescents' health attitudes and adherence to treatment for insulin-dependent diabetes mellitus (IDDM) were evaluated using the protection motivation theory (PMT). We expected cognitive appraisals of adherence (self-efficacy for treatment management, response efficacy of treatment, response costs of adherence) to be more influential for adherence than appraisals of nonadherence (rewards of nonadherence, perceptions of the risks of nonadherence, perceived severity of the risks). Adolescents (N = 101) with IDDM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 0 publications
4
45
1
Order By: Relevance
“…Higher perceptions of the seriousness of IDDM and weaker beliefs in the personal susceptibility to IDDM complications also are associated with better metabolic control (Brownlee-Duffeck et al, 1987). Higher perceptions of the severity of IDDM also have been related to better treatment adherence in one study (Palardy et al, 1998), while another study found it to be related to worse dietary self-care (Skinner et al, 2000). One explanation for these conflicting results is that these studies relied on possibly faulty self-report measures of adherence that ask the adolescent to recall their self-care behaviors over a certain period of time.…”
Section: Child Adaptational Processesmentioning
confidence: 86%
“…Higher perceptions of the seriousness of IDDM and weaker beliefs in the personal susceptibility to IDDM complications also are associated with better metabolic control (Brownlee-Duffeck et al, 1987). Higher perceptions of the severity of IDDM also have been related to better treatment adherence in one study (Palardy et al, 1998), while another study found it to be related to worse dietary self-care (Skinner et al, 2000). One explanation for these conflicting results is that these studies relied on possibly faulty self-report measures of adherence that ask the adolescent to recall their self-care behaviors over a certain period of time.…”
Section: Child Adaptational Processesmentioning
confidence: 86%
“…The Summary of Diabetes Self-Care Schedule (29) is a validated 12-item selfreport instrument that assesses four areas of diabetes self-management (diet, exercise, blood glucose monitoring, and injecting) over the previous 7 days, and it has been used previously with adolescents (18,20). The scales were scored by combining the scores for items contributing to the diet, exercise, and insulin injection scales.…”
Section: Methodsmentioning
confidence: 99%
“…Differentiating between long-and short-term beliefs may also be important in understanding the conflicting results for threat expectancies in previous work on adolescents with diabetes (18,20,25). Whether predicting anxiety, depression, or dietary self-management in adolescents, it was the short-term effects of the illness and its treatment (perceived impact of diabetes and effectiveness of treatment to control diabetes) that were important (19).…”
Section: Adolescent Personal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a theoretical guide, PMT has been used in etiological studies to investigate various risk and protective behaviors, including tobacco use [2,9], alcohol consumption [10,11], physical activity [12][13][14], self-care [15], safe and protective behaviors at the worksite [3,16], parental protective behavior [17], safe computing practices [18,19], and environmental hazard reduction [20]. As a conceptual framework, PMT has been utilized in intervention research in the West to develop and evaluate programs for purposeful behavior change, including interventions to promote adherence to medical treatment regimens [21,22], to prevent substance use [10,11], and to discourage HIV risk behaviors and encourage HIV protective behaviors [23][24][25][26].…”
Section: Research Guided By Pmtmentioning
confidence: 99%